Nomenclatural priority of the name Impatiens hirta over I. mohana (Balsaminaceae) - Ujwala, S.k.; Prabhukumar, K.m. (Phytotaxa, 2026)
Two names, Impatiens hirta L. Joseph & Bhaskar and I. mohana Ratheesh, Sujana & Anil., independently published in 2012 from the Wayanad district in the southern Western Ghats, India, are shown to represent the same species. Examination of the protologues, type material, additional herbarium specimens, and live populations revealed no consistent morphological differences between the two taxa. In accordance with the principle of priority under Article 11.4 of the ICN, the later-published name is here reduced to heterotypic synonymy.